Mendesain Meja Dan Kursi Ergonomi Dengan Mengacu Pada Nilai Antropometri Untuk Bagian Checking Rubber (Outsole) Di PT. Victory Chingluh Indonesia - Widodo, Tri; Fardiansyah, Ismail; Gufron, Ali (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2021)
PT. Victory Chingluh Indonesia is a company engaged in the manufacture of sports shoes in collaboration with an American brand, namely Nike. From the results of the Nordic Body Map Questionnaire at the PPIC RH department of the checking ruber section, many workers have complaints in the muscles (musculoskeletal disorders) due to non-ergonomic workplaces as many as 20 workers or 64.5% feel pain in the high category, as many as 8 workers or 25, 8% felt pain in the moderate category, for the category of pain with very high intensity as many as 2 workers or 6.4% and 1 worker or 3.2% felt pain in the low category. From these results, it is necessary to take further action by making ergonomic designs of Working Furnitures (tables and chairs) with reference to anthropometric values. With this reference, we get a table design with a length of 133.6 cm using the 5th percentile, a table width of 66.8 cm with a 5th percentile and a table height of 63.2 and a chair design with a chair height of 41.2 cm with a 50th percentile. -, the width of the seat base is 40.5 cm with the 95th percentile, it is expected that workers who have a maximum hip width can use the chair, the length of the seat base is 37.8 cm with the 5th percentile, the height of the seat back is 54.5 cm with the 50th percentile th and the width of the seat backrest is 48.9 cm with the 95th percentile. Keywords: Ergonomics, Anthropometry, musculoskeletal disorders. Nordic body map, design